Faculty perceptions of self-efficacy beliefs about facilitating discussions in small seminar classrooms: a mixed methods study - Leslie, Barry B. (Kansas State University, 2011)
This study examined faculty self-efficacy beliefs at the United States Army Command and General Staff College (CGSC) at Fort Leavenworth, Kansas. Faculty members at this military graduate degree-producing institution engaged in collaborative, student- centric, discussion teaching. The study considered how the independent variables of gender, age, ethnicity, academic title, leadership position, education level, and years of teaching experience affected faculty self-efficacy beliefs. Social cognitive theory provided the primary theoretical lens for the study. Discussion teaching and a framework for culturally responsive teaching formed part of the theoretical foundation. The goal included extending teacher self-efficacy concepts to higher education, further developing operational definitions, and providing an instrument suitable for measuring self-efficacy in higher education contexts. The study used mixed methods sequential explanatory research design with two data collection and analysis components: quantitative and qualitative. Faculty members (N = 417) received a 30-question Likert-type survey in December 2010. After quantitative data analysis concluded, in-depth interviews took place with 12 faculty members. A semi-structured interview of nine open-ended questions supported the qualitative portion of the study. Parametric analysis procedures examined the dependent variable, faculty self-efficacy beliefs, with respect to the independent variables. The results showed no significant differences in self-efficacy beliefs. Qualitative analysis using a computer-assisted program identified five themes: establishing a positive classroom environment, facilitating discussion, faculty and student preparation for discussion, questioning, and classroom sharing of combat and deployment experiences. Results of the study provided insights about faculty self-efficacy beliefs regarding facilitation of discussion that informed CGSC leadership decisions for future faculty development initiatives as well as insight for faculty to reflect on classroom best practices. The study contributed to the field of adult education by providing greater understanding of the faculty self-efficacy construct. Further research could examine faculty self-efficacy beliefs in non-military higher education contexts, among various faculty demographics and groups, and across higher education academic disciplines. Future studies could address how interventions such as faculty development or observation and feedback affect faculty self-efficacy beliefs in the classroom.
Keywords: Faculty Self-Efficacy Beliefs; Facilitation; Discussion Teaching; Mixed Methods; Army; Command and General Staff College; Education, General (0515)